ANTIOXIDANT AND HEPATOPROTECTIVE ACTIVITY OF SHILAJIT (ASPHALTUM PUNJABINUM) AGAINST ALCOHOL INDUCED LIVER INJURY IN WISTAR RATS - Subhash Chand Yadav,; Jeyabalan Govindasamy,; Reetesh Ramnani, (International Journal of Ayurveda and Pharma Research, 2020)
To investigate the antioxidant, hepatoprotective activity and evaluation of effects on blood factors of Asphaltum punjabinum demonstrable in-vivo and in-vitro by the inhibition of alcohol induced Wistar rat. In-vitro antioxidant activity of Asphaltum punjabinum was evaluated by various assays, including reducing power, lipid peroxidation, DPPH. Hepatoprotective activity as judged by the blood factors and serum enzymes levels viz. Serum Glutamate Oxaloacetate Transaminase (SGOT), Serum Glutamate Pyruvate Transaminase (SGPT), Alkaline Phosphatase (ALP), Total Bilirubin (TBIL) and Direct Bilirubin (DBIL) as well as oxidant enzyme viz. Malon Dialdehyde (MDA) were prevented, while antioxidant enzymes viz. Super Oxide Dismutase (SOD), reduced glutathione (GSH) and catalase were elevated in liver tissues. Further histopathological examination of liver sections was carried out to support the induction of hepatotoxicity and hepatoprotective efficacy. The results showed potent activities on reducing power, lipid peroxide, DPPH, Superoxide anion. The histopathological observations supported the biochemical evidences of hepato protection. Elevated level of SOD and decreased level of MDA further strengthen the hepatoprotective observations. In the study, demonstrating the Asphaltum punjabinum has potent antioxidant and hepatoprotective activity against alcohol induced hepatic damage in experimental animals.